Penggunaan Media “Wayang Perang” untuk Pemahaman Konsep Kalimat Matematika Siswa di Sekolah Dasar - Lailatussa’diyah, Lailatussa’diyah; El-Yunusi, M. Yusron Maulana (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Mathematics for elementary school students is useful for the interests of life in their environment, to develop their mindset, and to study later sciences. The usefulness or benefits of mathematics for elementary school students are clear and does not need to be questioned anymore, especially in the era of development of science and technology today. Based on ATP mathematics students can explain the steps to solve mathematical sentences with subtraction and addition on whole numbers up to 100. The purpose of this study is to provide students with an understanding of the concept of mathematical sentences using Wayang PERANG media. The research method used is descriptive qualitative. The subjects in this study were 28 students of grade III SDN Klurak Candi Sidoarjo. There are two sources of data used in this study, namely written test questions and interview results (as primary data sources) and documentation (as secondary data sources). Data analysis is in the form of data triangulation of test results, interviews, and observation results. The results of the study showed that the value of category 3 student abilities with a score of 76≤100 had a percentage value of 80.26%, and a score of 61≤75 still had 19.73% while a score of 0≤60 was still at the highest percentage value of 10.53%.